Dinamika Sumber Daya Manusia (SDM): Studi Tentang Turnover Karyawan Pada Rumah Makan Padang “Ananda” - Suistaya, Ilham Atim; Sutarman, Sutarman; Iskandarini, Iskandarini (Jurnal EMT KITA, 2025)
The high rate of employee turnover in the medium-scale culinary business sector is a serious challenge in the sustainability of business operations. This research aims to analyze the factors that cause turnover, its impact on operational performance, and formulate effective human resource management strategies at Ananda Padang Restaurant. The research approach used is descriptive qualitative with data collection techniques in the form of in-depth interviews, observation, and documentation. Data analysis was carried out through the stages of reduction, data presentation, and conclusion drawing, supported by a SWOT analysis approach. The results show that employee turnover is caused by a combination of internal factors such as a wage system that is not in accordance with the UMP, the absence of SOPs and job training, and high workload; and external factors such as family economic pressure, the young age of the workforce, and the phenomenon of labor migration abroad, especially to Cambodia and Malaysia. Turnover has a significant negative impact on service quality, team workload, and customer loyalty. Strategies formulated include the development of SOPs and work shifts, informal mentoring-based training, loyalty incentives, strengthening emotional communication, and education on the risks of illegal work. Managerial implications emphasize the importance of an adaptive, structured, and contextual HR management transformation in order to create a stable, healthy, and sustainable work environment.
Keywords: Turnover; HR Strategy; SWOT; Restaurant; Employee Management